Evaluation of hydro-geochemical processes controlling groundwater quality in Balkh center (Mazar-e-Sharif), northern Afghanistan - Asadullah Farahmand; Abdulhalim Zaryab; Nasrullah Ameri; Shakir Ali; Mohammad Naim Eqrar (Journal of Trace Elements and Minerals)
Background: Groundwater in Afghanistan stands as the predominant water source employed for potable consumption, household utilization, irrigation, and industrial applications. Major cities of Afghanistan are largely dependent on groundwater resources. However, the groundwater quality of major cities in Afghanistan, including Mazar-e-Sharif city was not investigated in detail. Objective: This study aims to conduct a comprehensive analysis of the hydrochemical characteristics of the Mazar-e-Sharif groundwater, identify the factors influencing groundwater quality, and evaluate the groundwater contamination sources. Methods: A total of 18 groundwater samples were collected during the dry season (June 2020) and analyzed for various physico-chemical parameters. Methods such as multivariate statistical analyses, geochemical modeling, water quality index (WQI), and spatial distribution of groundwater quality were employed to evaluate the hydro-geochemistry of the study area. Results: The results reveal that 1) The prevailing groundwater within the study area is predominantly characterized by Na-(Ca)-HCO3 and Ca-(Mg)-SO4 water types. 2) Physicochemical variables such as NO3−, F−, TDS, and SO42− exceeded the World Health Organization (WHO) safe limits in many wells. 3) Hydro-geochemical processes such as silicate weathering, cation exchange, and gypsum dissolution controls the groundwater chemistry. 4) Cl/Br ratios reveal, that high salinity may originate from evaporitic lacustrine and evaporite deposits and found to be localized in nature. 5) The Water Quality Index (WQI) classification suggests that approximately 60 % of the groundwater samples fall into poor to very poor water quality categories, highlighting substantial public health concerns. Major contaminants like nitrate and fluoride were found to be higher than the safe limit in nearly half of the samples. Conclusion: The findings of this study hold value for decision-makers in formulating a proficient strategy for the management of groundwater resources in Mazar-e-Sharif City in achieving the UN sustainable goal (SDG) of providing sustainable water for all. Furthermore, new advanced techniques like environmental isotopes should be analyzed to evaluate groundwater hydro-chemical evolution in the future to enhance our understanding.